2012
DOI: 10.1073/pnas.1211199110
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Mthfd1l causes embryonic lethality and neural tube and craniofacial defects in mice

Abstract: Maternal supplementation with folic acid is known to reduce the incidence of neural tube defects (NTDs) by as much as 70%. Despite the strong clinical link between folate and NTDs, the biochemical mechanisms through which folic acid acts during neural tube development remain undefined. The Mthfd1l gene encodes a mitochondrial monofunctional 10-formyl-tetrahydrofolate synthetase, termed MTHFD1L. This gene is expressed in adults and at all stages of mammalian embryogenesis with localized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
138
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 136 publications
(152 citation statements)
references
References 38 publications
9
138
1
Order By: Relevance
“…Formate export is essential in embryos, but not in adults (Tibbetts and Appling, 2010). Common single nucleotide variants in the MTHFD1 and MTHFD1L genes affect formate metabolism and are documented risk factors for neural tube defects, intrauterine growth restriction, congenital heart defects and neurodegenerative diseases (Parle-McDermott et al, 2009;Tibbetts and Appling, 2010;Momb et al, 2013).…”
Section: Formaldehyde Is Important For Folate-mediated One-carbon Metmentioning
confidence: 99%
See 1 more Smart Citation
“…Formate export is essential in embryos, but not in adults (Tibbetts and Appling, 2010). Common single nucleotide variants in the MTHFD1 and MTHFD1L genes affect formate metabolism and are documented risk factors for neural tube defects, intrauterine growth restriction, congenital heart defects and neurodegenerative diseases (Parle-McDermott et al, 2009;Tibbetts and Appling, 2010;Momb et al, 2013).…”
Section: Formaldehyde Is Important For Folate-mediated One-carbon Metmentioning
confidence: 99%
“…Export of mitochondrial formate is critical in mammalian embryonic development (Momb et al, 2013). Mitochondrial formate supplies~90% of one-carbon units incorporated into purines, thymidylate (dTMP) and other methyl groups.…”
Section: Formaldehyde Is Important For Folate-mediated One-carbon Metmentioning
confidence: 99%
“…Folate cycle enzyme MTHFD1L confers metabolic advantages in hepatocellular carcinoma Derek growth delay, neural tube and craniofacial abnormalities, and embryonic lethality (12). In humans, MTHFD1L polymorphisms are closely related to neural tube defects, coronary artery disease, and Alzheimer's disease (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Monofunctional 10-formyl-THF synthetase (MTHFD1L) is the mitochondrial enzyme responsible for the production of formate. Appling et al (5) have shown that knock-out of Mthfd1l is embryonically lethal, with embryos showing both growth defects and aberrant neural tube closure. Maternal supplementation of the drinking water with formate decreased the incidence of neural tube defects and partially rescued the growth defect (5).…”
mentioning
confidence: 99%
“…Appling et al (5) have shown that knock-out of Mthfd1l is embryonically lethal, with embryos showing both growth defects and aberrant neural tube closure. Maternal supplementation of the drinking water with formate decreased the incidence of neural tube defects and partially rescued the growth defect (5). These experiments provide strong evidence for a critical role for mitochondrially derived formate in mammalian development.…”
mentioning
confidence: 99%